2020
DOI: 10.1126/science.aba7365
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-engineered T cells in patients with refractory cancer

Abstract: CRISPR-Cas9 gene editing provides a powerful tool to enhance the natural ability of human T cells to fight cancer. We report a first-in-human phase 1 clinical trial to test the safety and feasibility of multiplex CRISPR-Cas9 editing to engineer T cells in three patients with refractory cancer. Two genes encoding the endogenous T cell receptor (TCR) chains, TCRα (TRAC) and TCRβ (TRBC), were deleted in T cells to reduce TCR mispairing and to enhance the expression of a synthetic, cancer-specific TCR transgene (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
860
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,062 publications
(967 citation statements)
references
References 56 publications
17
860
1
5
Order By: Relevance
“…This dream was further fueled by the discovery and repurposing of the bacterial and archaeal CRISPR-Cas immune systems which provided unprecedented genome editing capabilities 1 . Indeed, recent efforts have suggested that this promise is closer to reality than ever before as demonstrated through the ex vivo editing of human T cells for therapeutic purposes 13 . While this latter accomplishment may provide countless genetic treatments, the full potential of CRISPR-based therapeutic still will require a vehicle for in vivo editing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dream was further fueled by the discovery and repurposing of the bacterial and archaeal CRISPR-Cas immune systems which provided unprecedented genome editing capabilities 1 . Indeed, recent efforts have suggested that this promise is closer to reality than ever before as demonstrated through the ex vivo editing of human T cells for therapeutic purposes 13 . While this latter accomplishment may provide countless genetic treatments, the full potential of CRISPR-based therapeutic still will require a vehicle for in vivo editing.…”
Section: Discussionmentioning
confidence: 99%
“…This challenge is formidable, especially when one wishes to efficiently edit a large number of cells to repair a genetic defect in vivo . This problem is further confounded by the fact that maintaining Cas expression for longer periods of time can result in the generation of off-target effects, aberrant RNAs, chromosomal translocations, and/or removal of the Cas-expressing cells 12,13 . Given these challenges, the most optimal genetic editors would be delivered with the efficiency of a virus in a manner that was free of any possibility of genomic integration and would function only in a desired cell type for the time required to achieve editing.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying delivery efficiency and viability as important factors to generate effective cell therapies, the ability to synthesize a sufficient number of modified cells to dose patients is a critical factor in successful treatment in the appropriate time frame 2,3 . In our studies, we were able to generate >4.0…”
Section: Crispr-cas9 and µVsmentioning
confidence: 99%
“…As a proof of principle, the method showed safety and feasibility, even though the disease worsened in all patients, with one of them having died. 3 In the procedure, patients' own T-cells are harvested, and the endogenous T-cell receptors (TCR) are knocked out along with the PD-1 protein to prevent the cancer from downregulating the immune response. Next, a recombinant, NY-ESO-1-specific TCR is introduced and the cells are expanded and infused back into the patients.…”
Section: Crispr-engineered T-cells Used To Treat Cancer In An Early Smentioning
confidence: 99%